2017
DOI: 10.3329/bjar.v42i2.32808
|View full text |Cite
|
Sign up to set email alerts
|

Role of weather parameters on seasonal abundance of insects in a mangobased agroforestry in Bangladesh, with particular reference to mango hopper

Abstract: Weekly sweeping was done by sweep net in order to collect insects to study the effect of weather parameters on the seasonal abundance of total insect species as well as mango hopper population in a mango-based agroforestry in Bangladesh during January to June 2013. The total insect species abundance was the highest during April to May, following the flushing of inflorescence and fruit set. At that time temperature and relative humidity were comparatively higher and there was rainfall. Mango hopper population w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Weather factors greatly influenced the population dynamics of insects. A study by Namni et al (2016) showed that weather parameters contributed 61.7% abundance of hopper on mango plant. Dhaliwal et al (2007) stated that the incidence, growth and multiplication of mustard aphid are largely influenced by meteorological parameters like temperature, relative humidity, rainfall, wind speed and cloudiness.…”
Section: Resultsmentioning
confidence: 99%
“…Weather factors greatly influenced the population dynamics of insects. A study by Namni et al (2016) showed that weather parameters contributed 61.7% abundance of hopper on mango plant. Dhaliwal et al (2007) stated that the incidence, growth and multiplication of mustard aphid are largely influenced by meteorological parameters like temperature, relative humidity, rainfall, wind speed and cloudiness.…”
Section: Resultsmentioning
confidence: 99%
“…The results agreed with Amin et al (2015) who studied the insect abundance and diversity in a mango based agroforestry in Bangladesh and found that the Hemiptera were most abundant (59.8%). Namni et al (2017) observed the highest abundance of hopper compared to other insects in a mango based agroforestry. The findings indicated that the Hemipteroid pests were perhaps dominant on citrus, mango and pineapple during cooler and dry season.…”
Section: Resultsmentioning
confidence: 87%
“…Table V showed that the single effect of temperature, relative humidity and rainfall on the incidence of mealybug on dahlia was 14.4, 12.6 and 7.6%, respectively, and the collective effect of the weather parameters (34.6%) was statistically insignificant.Weather parameters predict varied levels of influence on phytophagous insects and affect their population dynamics in the current and next generations. Many authors reported varied levels of the impact of weather parameters on the incidences of sucking insects on crop plants (Sharma and Singh, 2012;Namni et al, 2017;Mandal et al, 2018;Mohammad et al, 2019).…”
Section: Table I Correlation Coefficient (R) Values Between Sucking Insect Population On Different Flowering Plants and Weather Parametermentioning
confidence: 99%